Simulating the Effect of Advertising on the Attraction of Medical Tourists with a Factor-Based Modeling Approach (Case Study: Yazd Hospitals) - Naser Seifollahi; Seyed Ali Naghavi (Tehran University of Medical Sciences, 2023)
Background: Nowadays, the medical tourism market is one of the most profitable and competitive industries in the world, and it is one of the new developed fields of tourism. Advertising is one of the methods of increasing tourist attraction and influencing tourists' decision-making to choose a destination. The present research aimed to simulate the effect of advertising on the attraction of medical tourists in the hospitals of Yazd city. Materials and methods: The present research is applied in terms of research objective, and in terms of methodology, it is in descriptive-analytical research. The statistical community was formed by university professors and experts in the field of medical tourism, and managers of hospitals and medical centers in Yazd. The snowball method was used for sampling. Information was collected through text reviews, questionnaires and semi-structured interviews with experts. The integrated and innovative approach of factor-based modeling and Taguchi method was used for data analysis, and the software used was AnyLogic and MiniTab. Results: The results of the scenario execution revealed that among the advertising tools, internet advertising is more effective, and television ads, specialized tourism magazines, and seminars and conferences are in the next ranks. As the final output of the research, the investigation of the main effects related to each advertising tool led to identification of the suitable level of each tools and the presentation of the most favorable scenario based on the advertising program of Yazd hospitals. Conclusion: Based on the fact that among the advertising tools, internet advertising has the greatest effect on attracting medical tourists, hospital management should pay special attention to internet advertising to attract more tourists in the field of medicine. In this way, more information will be provided to tourists and the demand for medical tourism will increase.